2009
DOI: 10.2341/08-009-l
|View full text |Cite
|
Sign up to set email alerts
|

Shear Bond Strength Evaluation of Resin Composite Bonded to GIC Using Three Different Adhesives

Abstract: SUMMARYThe current study evaluated the bonding ability of composite to glass ionomer cement (GIC) using three different bonding systems. One hundred samples of composites bonded to GIC were prepared and divided into five groups. In Group A, the composite was bonded to GIC after the initial setting of the GIC being employed as a total-etch adhesive. In Group B, the self-etch primer was employed to bond composite to GIC before the initial setting of the GIC. In Group C, the self-etch primer was employed to bond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 6 publications
4
49
1
5
Order By: Relevance
“…Zhang and others observed that total-etch adhesive has a lower bond strength than the self-etch adhesives when bonded to conventional GIC [20]. Gopikrishna and others showed that the bond strength of composite to GIC was significantly higher for the self-etch primer group employed on unset GIC [13]. But they observed superior performance of GIC based adhesive over set GIC which could be attributed to chemical bonding between the composites and resin modified glass-ionomers, which has been proven by previous reports [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang and others observed that total-etch adhesive has a lower bond strength than the self-etch adhesives when bonded to conventional GIC [20]. Gopikrishna and others showed that the bond strength of composite to GIC was significantly higher for the self-etch primer group employed on unset GIC [13]. But they observed superior performance of GIC based adhesive over set GIC which could be attributed to chemical bonding between the composites and resin modified glass-ionomers, which has been proven by previous reports [21].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have proven that self-etch systems produce bondstrength similar to total-etch systems to both dentin and enamel [11,12]. The other advantage of these systems is their feasibility to be employed over unset GIC, as there is no need to rinse the GIC prior to application of the bonding agent, thus preventing moisture contamination or desiccation of the underlying GIC and saving precious chairside clinical time [13].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the oxygen-inhibited layer is always produced when resin based material is polymerized in air 25) . The residual unreacted methacrylate groups on the polyacid chain within the oxygen-inhibited layer has been suggested to form strong chemical bonds with the resin composite 26,27) . Acid etching or air-abrasion of RMGIC can result in lower shear bond strength as these surface treatments may partially or completely remove methacrylate groups in the availability of the oxygen-inhibited layer, which contributes to copolymerization with resin composite.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of chemical bonding between composite resin and conventional GICs may interfere in the final properties of the restoration, and consequently, its longevity 6 . To improve the GIC/composite resin bond, the use of resin-modified glass ionomer cements may be indicated 3,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, moisture contamination during setting of the GICs may cause dissolution of the calcium polyacrylate chains altering their physical properties 9 , therefore it is advisable to wait for the initial setting to occur before carrying out the acid etching and washing 6,10 .…”
Section: Introductionmentioning
confidence: 99%